Application of edible coatings in conservation of acerola - Jorge Repolho, Ricardo Patrese; Oliveira, Wendel da Costa; Carvalho, Alexandre Pinto de; Sanches, Alex Guimaraes [UNESP]; Rodrigues de Sousa, Joao Thiago (Univ Estadual Centro-oeste, 2019)
The acerola is a tropical fruit recognized for its high nutritional value, however, the high pereceability after harvest motivated by its climacteric behavior requires conservation techniques that allow the maintenance of its quality during the storage period. The edible coatings, in this context, are presented as alternatives since they form barriers on the fruits, restricting the gas exchanges, improving the visual aspect without compromising with the fruit flavor. Thus, this study aims to evaluate the application of edible coatings on the post-harvest quality of acerolas cv. Costa Rica during refrigerated storage (10 degrees C). Fruits of ripe acerolas were harvested in a commercial orchard, sanitized and immersed in three solutions (3%) of cassava starch, arrow starch and gelatine, in addition to the control represented by uncoated fruits for a period of 3 minutes. These were then dried and packed in styrofoam polystyrene trays coated with polypropylene plastic film (PVC) and stored under refrigeration (10 degrees C) for 12 days. The total fresh solids content (degrees Brix), titratable acidity (% malic acid), pH, TSS/AT ratio and sensorial analysis on the occurrence of wilting were evaluated every three days, visual appearance and the aroma of the fruits. The experimental design was completely randomized in a factorial scheme of 4x5, that is to say, (4 treatments: control, cassava starch, arrowroot starch and gelatin) and (5 storage times: 0, 3, 6, 9 and 12 days), with five replicates and the experimental plot composed of 100 g trays. During the storage period, no significant difference was observed between the coatings used, however, their action on the fruits contributes to reduce the loss of fresh mass and to allow a better balance in the fruit flavor ratio (SST / AT) after 12 days. The films formed on the fruits did not compromise the chemical quality (soluble solids, titratable acidity and pH) maintaining similar behavior to the fruits of the control treatment. In addition, there was a reduction in the incidence of wilting and the loss of the characteristic aroma of the fruits, contributing to a better visual appearance. Thus, edible coatings based on cassava starch and arrowroot and gelatine are presented as effective alternatives in preserving the quality of acerolas during refrigerated storage.
Keywords: Malpighia emarginata DC.; biofilms; postharvest